2016
DOI: 10.1002/ird.2061
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of water and droplet size distribution from fluidic sprinklers

Abstract: A new prototype of fluidic sprinkler (PXH) is proposed and its working theory is reported. The hydraulic performance of four different types of sprinkler head (PXH, PY, Toro S 800 and RainBird S 3504) was compared at the same operating pressure. Meanwhile, PXHs with nozzle diameters of 4, 6 and 8 mm were tested to establish a mathematical model of water distribution and droplet diameter. The results show that the PXH produces the longest wetted radius, potentially due to its unique working principles. The PXH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The above outcomes suggested that the nozzle size and operating pressure had little effect on droplet diameters near the low‐pressure sprinkler, and their effects were mainly reflected in the droplet distribution in the latter half of the jet (Chen et al, 2020). Specifically, higher operating pressures corresponded to smaller volum‐ weighted average diameters at the same distance from the sprinkler, as previously reported by Ge et al (2020) on 50PYC and HY50 big gun‐type sprinklers and Liu, Yuan, et al (2016) on a PXH sprinkler. This is mainly because a larger sprinkler operating pressure will result in a faster jet velocity.…”
Section: Results and Analysissupporting
confidence: 83%
“…The above outcomes suggested that the nozzle size and operating pressure had little effect on droplet diameters near the low‐pressure sprinkler, and their effects were mainly reflected in the droplet distribution in the latter half of the jet (Chen et al, 2020). Specifically, higher operating pressures corresponded to smaller volum‐ weighted average diameters at the same distance from the sprinkler, as previously reported by Ge et al (2020) on 50PYC and HY50 big gun‐type sprinklers and Liu, Yuan, et al (2016) on a PXH sprinkler. This is mainly because a larger sprinkler operating pressure will result in a faster jet velocity.…”
Section: Results and Analysissupporting
confidence: 83%
“…The experiments were carried out in the irrigation laboratory of the Research Center of Fluid Machinery Engineering and Technology of Jiangsu University, China. The irrigation laboratory is an indoor windless test room with a diameter of 44 m and a height of 18 m. The laboratory can provide measurement and data acquisition conditions (Liu, Yuan, et al, 2016). The environmental temperature was 25°C during the test.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, it has a significant influence on the growth of crops and is one of the important indexes to evaluate the quality of sprinkler irrigation. Christiansen's uniformity coefficient (CU) was defined to evaluate sprinkler irrigation systems and has the strongest historical precedent in the sprinkler irrigation industry [23,24]. Christiansen's equation is defined as:…”
Section: Evaluation Indexmentioning
confidence: 99%